The Influence of Strategic Management and Work Discipline on Employee Performance at an Electricity Company in Indonesia - Afrianda, Dr. Rio (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
The purpose of this study is to identify the variables that most significantly influence employee performance in an electricity company in Indonesia. Furthermore, the impact of strategic management and work discipline on employee performance will be assessed simultaneously and independently in this study. The sample was randomly selected using purposive sampling, with a total of 77 employees. As part of the data collection method, questionnaires were administered to employees deemed suitable for the research. The data were analyzed quantitatively using six formulas (correlation analysis, t-test, F-test, dominance test, multiple linear regression analysis, and coefficient of determination (R2) using SPSS 20 software. The findings indicate a substantial relationship between work discipline and Strategic Management, both individually and collectively, and employee performance in electricity companies in Indonesia. A positive correlation is evident in the regression coefficient with a positive (+) value between work discipline and Strategic Management. In other words, these two elements will increase employee output in electricity companies in Indonesia. Work discipline, Strategic Management, and employee performance have a strong correlation (r = 0.867) and a coefficient of determination (0.752) in electricity companies in Indonesia. Furthermore, work discipline is the most influential factor on employee performance.